La prévalence de la neutropénie fébrile chimio-induite chez les enfants cancéreux de sud algérien - Maazouz BENSALEM; Kouider DAHINI (Université Amar Telidji de Laghouat Faculté de Médecine, 2022)
Febrile neutropenia consecutive to the administration of chemotherapy constitutes the most serious and the most frequent complication of cytotoxic chemotherapies. It is often a sign of infection, being able to quickly turn in septicemia if no treatment is begun; it thus constitutes an urgency diagnosis and therapeutics. The objective of this work is to study the epidemiological, clinical, biological, etiologic and evolutionary characteristics of the episodes of febrile neutropenia, to evaluate the importance of the infectious risk and the main involved germs, to identify the difficulties of the management and the follow-up of the children having developed a febrile neutropenia and finally. During our retrospective study concerning the episodes of febrile neutropenias diagnosed in the pediatric oncology unit of the pediatric department of the university hospital of Alger over a period of 04 years (from 1 January 2017 to 31 December 2020). 205 patients having solid tumor were collected. Among them 45 cases presented febrile episodes, the average age was 5.75 years with a maximum frequency of them were male, and the main motive for consultation was the fever. The average deadline of occurrence of neutropenia was of 14.6 days. A documentation of the fever is obtained clinically at 20 % of the cases, while in 80 % of the cases, the fever remains unknown origin. The infectious sites found are: Skin (6.6%), digestive (4.4%), respiratory (8.8%). The average duration of the neutropenia was of 18.8 days. Upon completing this work, we emphasize the need of prompt and appropriate management of the hematological emergency that is febrile neutropenia by an adapted empirical antibiotic therapy after a good bacteriological investigation, without forgetting the importance of prophylaxis based mainly on hygienic mucocutaneous measures and the information/education of parents about the risk of infection and means of prevention.
86 p.